1977
DOI: 10.1002/aic.690230203
|View full text |Cite
|
Sign up to set email alerts
|

A group contribution molecular model of liquids and solutions

Abstract: A = a = = ideal gas state Subscripts c = critical property i, i, k = component identifications o = reference state A group contribution molecular model is developed for the thermocluding energy of vaporization, pVT relations, excess properties, and activity coefficients. The model is based on the cell theory in which the repulsive forces of molecules are expressed with a modified cell partition function derived from the Carnahan-Starling equation of state for hard spheres. The attractive forces are made u p of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
125
0
2

Year Published

1979
1979
2000
2000

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(133 citation statements)
references
References 43 publications
(31 reference statements)
2
125
0
2
Order By: Relevance
“…In previous papers (3,4) we have determined the characteristic parameters for carbonate and methyl, or methylene groups of the UNIFAC model (in the versions of Dang and Tassios, (5) Larsen et al (6) and Gmehling et al (7) ) and the Nitta-Chao (8) model. Our next step is to determine the carbonate-aromatic parameters for several group contribution models.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers (3,4) we have determined the characteristic parameters for carbonate and methyl, or methylene groups of the UNIFAC model (in the versions of Dang and Tassios, (5) Larsen et al (6) and Gmehling et al (7) ) and the Nitta-Chao (8) model. Our next step is to determine the carbonate-aromatic parameters for several group contribution models.…”
Section: Introductionmentioning
confidence: 99%
“…A recent series of studies (1)(2)(3) dealing with binary systems of (an alkyl ester + an n-alkane) have shown that the results of modeling of the mixtures using the UNIFAC, (4,5) DISQUAC, (6) and Nitta et al (7) group-contribution models become less accurate with increasing length of the aliphatic chain R 1 or R 2 in esters of the type R 1 COOR 2 and a To whom correspondence should be addressed (E-mail: jortega@cicei.ulpgc.es). also with increasing molar mass of the n-alkane.…”
Section: Introductionmentioning
confidence: 99%
“…For (an a,v-dichloroalkane+an n-alkane) both H E and V E decrease with the a,v-dichloroalkane size. (12,(17)(18)(19) Recently Garcı´a et al (19) determined interaction parameters which depend regularly on the distance between the Cl atoms for (a,v-dichloroalkane+alkane) in the framework of the Nitta-Chao (20) the application of the Nitta-Chao model to complete the analysis of the behaviour of these mixtures.…”
Section: Discussionmentioning
confidence: 99%